IMPLEMENTASI PROGRAM PERTUKARAN MAHASISWA OUTBOUND DI UNIVERSITAS MUHAMMADIYAH SIDENRENG RAPPANG - Andi Feby Febriani; Muhammad Ikbal; Erfina (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2023)
The purpose of this research is to examine how the Independent Student Exchange Program at Muhammadiyah Sidenreng Rappang University in 2022 will implement government policies and build capabilities. This study uses the theory of Edward III. The theory of policy implementation is presented using a case study methodology and a qualitative research style. Participants in the Free Student Exchange program are research subjects, along with lecturers. Direct observation and interviews are the two data collection methods used. N-Vivo 12 Plus is used to perform data analysis. Implementation of state requirements for independent student exchanges is going well, as faculty and staff work together to fulfill their duties. In addition, the campus bureaucracy has several obstacles, especially in organization and communication.